Particles swarm optimization-simulated annealing (PSO-SA) with mass extinction applied to nonlinear optimization problems - Jopson, Maria Andrea Aizza Galon (2009)
Particle Swarm Optimization ? Simulated Annealing (PSO-SA) with Mass Extinction is an extension of Xie?s et.al.?s (2002), which searches for a hybrid technique that will get an optimal solution in numerical problems in evolutionary optimization research. PSO-SA with Mass Extinction is a combination of heuristic, meta-heuristic and evolutionary algorithms that aims to solve underlying problems in solving underlying problems in solving evolutionary problems. This hybrid algorithm will be tested three benchmark evolutionary functions namely; Rosenbrock function, Rastrigin function and Griewank function
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2009
Keywords: Optimization; Particle Swarm Optimization-Simulated Annealing (PSO-SA); Simulated annealing